Topic analysis of nursing research using co-word analysis - Ali Akbar Khasseh; Mohammad Reza Amiri; Amir Sadeghi (Wolters Kluwer Medknow Publications, 2021)
Background: Nursing is one of the most important areas of medical sciences whose developments including its scientific publications can influence health care. Therefore, the aim of this study was to investigate nursing articles published from 2013 to 2018, and to provide a comprehensive view of common topical clusters in this research area. Materials and Methods: In this practical research, bibliometrics method and co-word analysis technique are used. The study population included all the articles in nursing area indexed in Web of Science from 2013 to 2018. The bibliometrics software, including BibExcel, UCINET, and SPSS was used to analyze the data. Results: Results indicated that the most frequently used nursing words in nursing research articles were "Quality of life," "Aged," "Education," and "Nursing." Moreover, the pairs such as "Anxiety-Depression", "Education, Nursing-Students, Nursing" and "Depression--Quality of life" were the most frequent co-occurrences. The use of hierarchical clustering led to the formation of seven topical clusters in Nursing: "Nursing care for the Aged," "Self-care," "Physical, emotional, and social support, "Mother and child health," "Preventing nursing care," "Nursing profession Research," and "Quality of nursing care." Conclusions: The growth of nursing scientific productions is an indicative of the importance of this subject area in healthcare services; however, there is no balanced growth in various subjects.